Chiral phosphorus-containing calixarenes. (27th May 2019) - Karpus, Andrii; Yesypenko, Oleksandr; Cherenok, Sergii; Boiko, Vyacheslav; Kalchenko, Olga; Voitenko, Zoia; Trybrat, Oleksandr; Poli, Rinaldo; Daran, Jean-Claude; Manoury, Eric; Kalchenko, Vitaly
Abstract: Phosphorus-containing inherently chiral calix[4]arenes as well as calix[4]arenes substituted with phosphinoferrocene chiral groups at the lower rim are described. Stereoselective synthesis, structure, and catalytic properties of the chiral calixarenes are discussed. Graphical Abstract: uf0001